2016
DOI: 10.1002/prop.201600080
|View full text |Cite
|
Sign up to set email alerts
|

String consistency, heavy exotics, and the 750 GeV diphoton excess at the LHC

Abstract: String consistency conditions are stronger than anomaly cancellation and can require the addition of exotics in the visible sector. We study such exotics and demonstrate that they may account for the modest excess at 750 GeV in recent diphoton resonance searches performed by the ATLAS and CMS collaborations. In a previous analysis of type II MSSM D-brane quivers we systematically added up to five exotics for the sake of satisfying string consistency conditions. Using this dataset, we demonstrate that 89780 of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 161 publications
(236 reference statements)
0
21
0
Order By: Relevance
“…In supersymmetry, the scalar partner of the goldstino could provide an explanation to the diphoton signal [97,147,167,335]. Other ideas, slightly more exotic, include: a model with a space-time varying electromagnetic coupling constant [135], Gluinonia [337], Squarkonium/Diquarkonium [299], flavons [244], axions in various incarnations [8,24,63,246,274,336], a natural Coleman-Weinberg theory [22,307], radiative neutrino mass models [264,325,327], and string-inspired models [19,132,188,240,254].…”
Section: Modelsmentioning
confidence: 99%
“…In supersymmetry, the scalar partner of the goldstino could provide an explanation to the diphoton signal [97,147,167,335]. Other ideas, slightly more exotic, include: a model with a space-time varying electromagnetic coupling constant [135], Gluinonia [337], Squarkonium/Diquarkonium [299], flavons [244], axions in various incarnations [8,24,63,246,274,336], a natural Coleman-Weinberg theory [22,307], radiative neutrino mass models [264,325,327], and string-inspired models [19,132,188,240,254].…”
Section: Modelsmentioning
confidence: 99%
“…In figure 6 we depict the maximal diphoton cross section as a function of the lightest charged vector particle mass (either a lepton or a slepton) and of the lightest colored vector particle mass (right panel). 11 In the left panel, we required (s)quark masses of at least 700 GeV, in the right panel slepton masses of at least 380 GeV. In addition, the fermion mass ratios of table 3 were imposed.…”
Section: Predictions For Lhc-13mentioning
confidence: 99%
“…It remains to be shown that the part of parameter space, in which a sufficient diphoton signal arises, is accessible within grand unified theories. Therefore, we have chosen to implement the model with a singlet and one 10 + 10 into 12 More restrictive numbers which circulate in the literature have been obtained under the assumption of a larger diphoton cross section. Table 5.…”
Section: From the Gut Scale To The Weak Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Though further data is required to establish the existence of a new resonance or other beyond the SM (BSM) mechanism responsible for the diphoton excess, significant theoretical efforts have been made to explain the possible diphoton excess in various BSM scenarios [4-9,11-13,15-a e-mail: jgao@anl.gov b e-mail: zhanghao@physics.ucsb.edu c e-mail: zhuhx@mit.edu 19,[26][27][28][29][30][32][33][34]38,[41][42][43][44][45][48][49][50][51][52][53][54][55][56][57]59,63,[65][66][67][68][69]71,72,[75][76][77][78][79][80][83][84][85][86][87]89,90,[93]…”
Section: Introductionmentioning
confidence: 99%